EXTRACTION AND GCIMS ANALYSIS OF THE ESSENTIAL OIL OF OCIMUM BASILICUM (CaMaRa) - RIAZ, M.; KHALID , M. RASHID; HANIF , M.; CHAUDHARY , F. M. (Biological Sciences - PJSIR, 2022)
A combination of GC ane!GC/MS has been used to characterise chemical composition or essential oil hydrodistilled from comoro variety of Ocimum basilicum grown in various parts of Pakistan. Among the forty four compounds identified, methyl chavicol (83.58-87.21 %), I, 8-cineol (2.45-3.37%), tinalool (0.04 - 2.69%) and methyl eugenol (1.4 - 2.68%), are predominantly present while other compounds particularly monoterpenes and sesquirerpencs hydrocarbons are found only in traces. Variations in the essential oil composition ami yield during hydrodistillation are also reported.